Air-sensor concrete poker vibrator - Hadi Hassan, Muhammad Nazhan; Ishak, Noor Rizallinda (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Vibrating concrete is a crucial process of compacting, that impacts the quality of concrete. The existing monitoring method relies on workmanship. Concreter measures based on visual inspection and experiences. This approach is subjective and can be easily manipulated. Rectifying works can only be done after the concrete hardened, which is impossible to identify inadequate compaction alongside poor workmanship right away. Therefore, this study offers an idea of how to tackle the monitoring system for concrete compaction and workmanship quality. The development of an Air Sensor Concrete Poker Vibrator is focused on addressing the challenges in the construction, especially for Industrial Building System (IBS) Formwork Panels. The objectives proposed are to prevent defects and reduce repair work. Data collection was done by applying literature reviews and simulation studies. The marketability potential of the innovative product aligns with Sustainable Development Goals (SDGs) and offers technological advancement that can benefit the construction industry globally. This research methodology is intended to provide a structured approach to developing and evaluating the proposed technological innovation. The research concludes that the Air Sensor Concrete Poker Vibrator is a valuable addition to the construction industry for achieving higher standards of quality and sustainability.